The use of correspondence analysis in the study of beef quality: a case study on Parda de Montaña breed - Panea, B.; Casasús, I.; Blanco, M.; Joy, M. (Spanish Journal of Agricultural Research, 2009)
The present study shows the usefulness of a multivariate technique -correspondence analysis– for simultaneously representing continuous and categorical variables in graphical form. A comparison was made of the results of sensory tests of beef quality performed by a trained panel and by consumers. The latter included the collection of data to produce consumers profiles and the recording of a number of consumers habits. Spearman correlation coefficients were calculated independently for the variables measured in both the panel and consumer tests. Two correspondence analyses were then performed: the first one involving the consumer profiles and the values of the variables measured in the consumer test, the second one to determine the relationships between the panel and consumer test scores. In the plot corresponding to the first analysis, the two axes accounted for 52.2% of the inertia and showed that age did not have an important effect on any measured variable. Consumers previous experience has been shown to be an important factor defining consumer liking of the product. In the plot for the second analysis the two axes accounted for 82.3% of the inertia and showed that there was no correspondence between overall consumer liking of the product and any of the panel variables. These results therefore suggest that the panel test is not a good predictor of consumer behaviour.